The Concept of Character Education According to the Qur'an and Hadith Qualitative Analysis of Previous Studies - Khodijah, Siti; Imama, Isrofeni; Tusyahri, Alfiah; Rahma, Annisa Aulia; Permatasari, Mia (Qur'an and Hadith Academic Society, 2024)
Abstract: This study analyzes the concept of character education according to the Qur'an and Hadith through qualitative studies of various previous studies. Character education is a crucial aspect in shaping individuals who have moral integrity and social responsibility. In the context of Islamic education, the Qur'an and Hadith are the main sources that establish the values and principles of good character formation. The Qur'an provides basic guidance, while the Hadith provides concrete examples of these teachings. This study explores the values and methods of character education contained in the Qur'an and Hadith, as well as their relevance in the context of formal and informal education. The findings of the research are expected to make a significant contribution to the understanding and implementation of character education rooted in Islamic values, with the ultimate goal of creating Muslim individuals with noble character and an ethical society.